Kulturellt utbyte eller billig arbetskraft? - au pair i Sverige (Sociologisk Forskning, 2002)
Cultural exchange or cheap labour power? Au pairs in SwedenDuring mid 1980’s domestic services were re-introduced in Sweden. It is mostly the dual-career families that demand these services because of the unchanged gender division of labour in the households and their particular career life-styles. An au pair system has established itself in Sweden and many au pairs are recruited from Eastern Europe. This form of domestic service is hidden behind formal rules, stating that the purpose of the au pair system is to let young people get to know Sweden and to learn the Swedish language. Instead, the au pair’s are being used as cheap labour power without being entitled to any labour or civil rights. In this example of commodification though, labour power is not totally disembodied. It is embodied in the sense that some social categories are looked upon as more suitable than others for performing paid household work.